(untitled) (Ex Chordis, 2024)
This article aims to analyze the historical and musical context in which the young Hindemith, born in a period of political and social upheaval in Germany at the turn of the 19th and 20th centuries, embarked on the path that would eventually make him one of the most important musical figures of his time. Although still far from his full artistic maturity, we will explore a small part of his early years, during which the composer made perhaps the most radical change of his career. Hindemith embraced the innovations brought by the previous generation, opening his writing to profound reflections on form and the inclusive possibilities of tonality. From that period, specifically in 1919, we will see how in the Sonata Op. 11 No. 4 he began the gradual expansion of his linguistic conception, where he experimented with reshaping traditional forms, especially those of the German tradition; playing with few elements while simultaneously constructing a discourse of great expressive and compositional variety. Subsequently, in an era of great changes and artistic fervor like that of the 1920s and 1930s, the young composer found himself making choices that initially placed him among the composers adhering to the expressionist aesthetic, with Schönberg being the most prominent figure, which in a few years would lead to the theorization of twelve-tone technique. However, Hindemith soon abandoned the direction taken by the founder of the Second Viennese School to embark on a completely personal path: the “New Objectivity.”